2023
DOI: 10.1039/d2em00526c
|View full text |Cite
|
Sign up to set email alerts
|

A multi-pathway exposure assessment for polycyclic aromatic hydrocarbons among residents in the Athabasca oil sands region, Canada

Abstract: Due to increasing emissions from ongoing development of the oil sands in northern Alberta, Canada, there is concern that local residents and organisms are experiencing elevated exposures to hazardous contaminants....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…As we learn from parent PAHs, diet typically accounts for at least 90% of their intake among nonsmoking adults, while exposure via air, water, and soil contributes only ∼4% to the total dose of carcinogenic PAHs. However, in regions with significant atmospheric PAH pollution, such as Beijing, China, dietary contribution can be less (∼70%) . The overall potential dose of carcinogenic PAHs for adult males who are nonsmokers is estimated to be about 3 μg/day at the median and 15 μg/day at the maximum .…”
Section: Identification and Occurrences Of Pah Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…As we learn from parent PAHs, diet typically accounts for at least 90% of their intake among nonsmoking adults, while exposure via air, water, and soil contributes only ∼4% to the total dose of carcinogenic PAHs. However, in regions with significant atmospheric PAH pollution, such as Beijing, China, dietary contribution can be less (∼70%) . The overall potential dose of carcinogenic PAHs for adult males who are nonsmokers is estimated to be about 3 μg/day at the median and 15 μg/day at the maximum .…”
Section: Identification and Occurrences Of Pah Derivativesmentioning
confidence: 99%
“…However, in regions with significant atmospheric PAH pollution, such as Beijing, China, dietary contribution can be less (∼70%). 49 The overall potential dose of carcinogenic PAHs for adult males who are nonsmokers is estimated to be about 3 μg/day at the median and 15 μg/day at the maximum. 50 In studies examining nonsmoking male university students, it was found that the amount of 1-OHP, which is an exposure biomarker of PAHs, excreted in urine was strongly associated with dietary PAH exposure but not with inhalation exposure.…”
Section: Derivativesmentioning
confidence: 99%
“…1,2 Pb exposure occurs by eating, inhalation, cutaneous absorption, and transplacental absorption. 3,4 Globally, Pb exposure remains a significant public health concern, particularly in low and middle income countries. According to the World Health Organization, 5 Pb exposure contributes to approximately 540 000 mortality every year, with the highest number in sub-Saharan Africa due to environmental pollution from mining, industrial activities, and use of Pb-containing products.…”
Section: Introductionmentioning
confidence: 99%